The Processing of Glycerol with Acetone to Produce Solketal Using Amberlite IR 120 Na Catalyst: Comparison of solketal Production Using Gas Chromatography - Fikrah D. I. Sawali; Hary Sulistyo; Wahyudi B. Sediawan; Moh. A. Afandy (Universitas Tadulako, 2022)
Solketal is a chemical that can be made by combining glycerol with acetone. This compound can be used as a fuel oil additive to improve the cold flow properties of liquid transportation fuels, reduce specific emissions, aid in the reduction of gum formation (oil sap), increase oxidation stability, and increase the octane number by up to 2.5 points to accelerate the initiation process in motor fuel combustion. The addition of solketal, a bio-additive material in biodiesel, is expected to reduce emissions from diesel engines. Solketal can reduce glycerol waste created from biodiesel synthesis in addition to reducing resultant emissions because glycerol waste can be used as the primary raw material in the process manufacture of the solketal. The purpose of this research is to find out The catalytic process of glycerol and acetone using Amberlite IR 120 Na catalyst was traced using gas chromatography analysis. Solketal formation analysis using gas chromatography was used in this study. According to the results of gas chromatography analysis, the solketal produced without going through the distillation process has a purity of 23.54%, while the solketal produced after going through the distillation process has a purity of 38.94% when compared to the synthetic solketal produced by Sigma Aldrich, which has a purity of 95.67%. To manufacture solketal with a higher level of purity, the batch method was improved by adding a distillation process step to remove the water content and acetone that was still present in the sample.